Job Satisfaction and Burnout Risk Among American and Turkish Counselor Educators - Dean W. Owen; Ayhan Demir (Istanbul Kültür University, 2015)
The roles required of university teaching faculty have evolved quite dramatically over the past half century. With this evolution in role and function has come increasing demands for productivity, efficiency, learning new delivery platforms and responding to the ever changing demands of higher education. This study compared a sample Turkish (n = 91) counselor education faculty members with a sample of their U.S. counterparts (n = 90) with regard to job satisfaction and burnout risk. Data were collected through the use of an online survey and results revealed significant differences between the samples. Results indicated significant differences between samples in job satisfaction levels as well as a negative relationship between burnout risk and satisfaction. Discussion of findings and implications for further research were presented.